INTRODUCING MODERN PEDESTRIAN CROSSINGS TO ENSURE TRAFFIC SAFETY ON ROADS - Khaydarali Fayzullayev (Western European Studies, 2025)
Ensuring pedestrian safety remains a pressing issue in urban traffic management, particularly in developing countries where road infrastructure is rapidly evolving. This study aims to explore the role of modern pedestrian crossings in enhancing road safety and reducing the frequency of pedestrian-involved traffic accidents. The research utilizes a comparative analytical method, examining pedestrian infrastructure models from countries with successful traffic safety records and comparing them to current practices in Uzbekistan. Particular attention is given to illuminated crosswalks, intelligent traffic light systems, and accessibility features for people with disabilities. The findings indicate that the integration of smart pedestrian crossing systems can significantly improve visibility and reaction time, thereby decreasing accident rates. The article concludes by recommending a phased implementation strategy for modern pedestrian infrastructure in densely populated and high-risk zones, emphasizing the need for legal, technical, and public awareness reforms. The proposed approach supports national goals for sustainable urban mobility and contributes to the development of a safe, inclusive, and efficient road environment.
Keywords: pedestrian safety; smart crossings; urban traffic